Study of impairment in collaboration between ceruloplasmin and transferrin in development of complications in type 2 diabetes mellitus - Sharma, Reenu; Patani, Sunil S.; Nayak, Maulik S. (International Journal of Research in Medical Sciences, 2017)
Background: Hyperglycemia in diabetic patients can increase the levels of free radicals through various metabolic alterations. One of the most reactive pro-oxidants in peroxidation reactions is free, redox-active iron and generates highly reactive hydroxyl radicals that initiate lipid peroxidation. The purpose of the study was to elucidate the role of CP and TRF in type 2 DM and analyse the effect of disturbance in collaboration between these parameters in pathogenesis of type 2 diabetic complications. Methods: We included 100 Type 2 DM subjects (with and without complications) and 100 healthy controls. The duration of type 2 DM in study subjects ranged from 5 to 16 years. Blood samples in fasting condition were collected for analysis of serum malondialdehyde (MDA), CP and TRF. Results: In the study serum CP levels were higher in Type 2 diabetic subjects with complications compared to diabetic subjects without complications (P=0.01). However, significantly low transferrin values were obtained in diabetic subjects with complications compared to diabetic subjects without complications (P=0.007). Significantly high MDA levels were observed (P=0.002) in type 2 diabetic subjects with complications compared to type 2 diabetic subjects without complications. Conclusions: The results of the present study indicate oxidative stress plays a role in precipitating complications in Type 2 DM reflecting in disturbance of CP and TRF collaboration.